2023
DOI: 10.2147/dddt.s392569
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Remimazolam on Postoperative Delirium in Older Adult Patients Undergoing Orthopedic Surgery: A Prospective Randomized Controlled Clinical Trial

Abstract: Background: Postoperative delirium is common in older adult patients and associated with a poor prognosis. The use of benzodiazepine was identified as an independent risk factor for delirium, but there is no randomized controlled trial regarding the relationship between remimazolam, a new ultra-short acting benzodiazepine, and postoperative delirium. We designed a randomized controlled trial to evaluate if remimazolam increases the incidence of postoperative delirium compared with propofol in older adult patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
8

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 46 publications
0
13
0
8
Order By: Relevance
“…15 In addition, compared with dexmedetomidine, remimazolam is also effective in reducing the incidence of EA in elderly patients after orthopedic surgery. 16,17 The results also showed that there was no signi cant difference in extubation time and length of PACU stay between the two groups. This may be related to the pharmacological properties of remimazolam, which has been con rmed by multiple studies to have no effect on postoperative recovery time.…”
Section: Discussionmentioning
confidence: 87%
“…15 In addition, compared with dexmedetomidine, remimazolam is also effective in reducing the incidence of EA in elderly patients after orthopedic surgery. 16,17 The results also showed that there was no signi cant difference in extubation time and length of PACU stay between the two groups. This may be related to the pharmacological properties of remimazolam, which has been con rmed by multiple studies to have no effect on postoperative recovery time.…”
Section: Discussionmentioning
confidence: 87%
“…Further evidence related to delirium in older patients and procedural sedation, such as general anesthesia in clinical practice, is essential for clarification of the pros and cons of using remimazolam for procedural sedation in older patients. Yang et al reported that general anesthesia with remimazine in older patients undergoing orthopedic surgery did not result in an increase in postoperative delirium compared with propofol [ 33 ]. Recently, research on remimazolam has been increasing.…”
Section: Discussionmentioning
confidence: 99%
“…Duan et al enrolled 60 elderly patients who had hip replacement to show that remimazolam anesthesia, when compared with propofol anesthesia, could reduce the incidence of emergence agitation [ 38 ]. Another recent study found that remimazolam anesthesia did not increase POD among elderly patients undergoing orthopedic surgical procedures [ 39 ]. However, the role of remimazolam in cardiac surgery and its impact on POD are largely unknown.…”
Section: Discussionmentioning
confidence: 99%